Influence of foot positions on the spine and pelvis - Betsch, Marcel; Schneppendahl, Johannes; Dor, Larissa; Jungbluth, Pascal; Grassmann, Jan Peter; Windolf, Joachim; Thelen, Simon; Hakimi, Mohssen; Rapp, Walter; Wild, Michael (Arthritis and Rheumatism, 2011)
Objective. The management of knee osteoarthritis includes the use of wedged shoe insoles to unload the affected knee compartment. Although the biomechanical effects of shoe insoles on the knee joint are known and described, only little is known about their influence on the pelvis and spine. Therefore, the purpose of this study was to evaluate the effects of different foot positions, such as how they could be achieved by shoe insoles, on pelvic position and spinal posture. Methods. A total of 51 test subjects were measured for this study. The different foot positions (inner and outer margin increase, positive and negative heel height) were simulated with a specially designed stand platform. A rasterstereographic device was used to measure the immediate effects of the simulated foot positions on the pelvic position and spinal posture. Results. Positive and negative heel heights as well as an increase of the outer margin of the platform led to significant changes of the pelvic tilt. The pelvic torsion also changed significantly during positive heel height changes of 10 and 15 mm and increases of the outer margin of the foot. No significant changes were found between foot position and spinal parameters. Conclusion. The results of our study support the existence of a kinematic chain, where changes of foot position also led to significant alterations of the pelvic position. Whether these changes could lead to long-term pathologic alterations still needs to be evaluated. However, in our setting, no correlation between foot position and spinal posture changes was found. © 2011, American College of Rheumatology.
CRIS-Team Scopus Importer:2022-07-20